Genetic Analysis of Patients With Early-Onset Parkinson’s Disease in Eastern China - Hua, Ping; Zhao, Yuwen; Zeng, Qian; Li, Lanting; Ren, Jingru; Guo, Jifeng; Tang, Beisha; Liu, Weiguo (Frontiers in Aging Neuroscience, 2022)
Background: Genetic factors play an important role in the pathogenesis of early-onset Parkinson’s disease (EOPD). To date, more than 20 pathogenic genes of Parkinson’s disease (PD) have been identified. This study aims to explore the mutation spectrum of EOPD and the clinical characteristics of mutation carriers in eastern China. Methods: We recruited 155 unrelated EOPD patients, including 8 familial and 147 sporadic EOPD (age at onset ≤ 50 years). 24 known PD-associated genes were detected by whole exome sequencing and multiplex ligation dependent probe amplification (MLPA) from patient samples. The genetic and clinical characteristics of pathogenic/likely pathogenic (P/LP) loci in this cohort were analyzed. Results: 14 (9.03%) patients were detected with P/LP variants distributed in 7 genes. The most frequent mutation occurred in PRKN (7/155, 4.52%), followed by LRRK2 (2/155, 1.29%), SNCA, CHCHD2, TMEM230, DNAJC13 and PLA2G6 (1/155, 0.64%, respectively). Exon rearrangement mutations accounted for 57.9% (11/19) of all mutations in PRKN. Four novel variants were detected: c.14T>C (p.M5T) in SNCA, c.297C>A (p.Y99X) in CHCHD2, c.2578C>T (p.R860C) in DNAJC13 and c.4C>T (p.Q2X) in TMEM230. We found the first case of LRRK2 c.6055G>A (p.G2019S) mutation in Chinese population. The median onset age of patients with P/LP mutations in autosomal recessive genes (PRKN and PLA2G6) were about 18.0 years earlier than patients without mutation. The proportion of patient with mutation was 63.64%, 27.03% and 9.68% when patients were stratified according to age of onset at ≤30, ≤40 and ≤50 years, respectively. Conclusions: EOPD patients from eastern China presents a regional specific mutation spectrum. Analyses of larger patient cohorts are required to support these findings, and mechanistic studies of the four novel missense/nonsense mutations will clarify their role in the pathogenicity of EOPD.